2014
DOI: 10.1002/jmrs.61
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying intra‐ and inter‐fractional motion in breast radiotherapy

Abstract: IntroductionThe magnitude of intra- and inter-fractional variation in the set up of breast cancer patients treated with tangential megavoltage photon beams was investigated using an electronic portal imaging device (EPID).MethodsDaily cine-EPID images were captured during delivery of the tangential fields for ten breast cancer patients treated in the supine position. Measurements collected from each image included the central lung distance (CLD), central flash distance (CFD), superior axial measurement (SAM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
3
17
1
Order By: Relevance
“…(a) is without OSMS and (b) is with OSMS portal imaging was used for relative measurements to get a more realistic intrafraction motion and they report intrafraction motion to be less than 1 mm and comparable to our results 13. (a) is without OSMS and (b) is with OSMS portal imaging was used for relative measurements to get a more realistic intrafraction motion and they report intrafraction motion to be less than 1 mm and comparable to our results 13.…”
supporting
confidence: 81%
“…(a) is without OSMS and (b) is with OSMS portal imaging was used for relative measurements to get a more realistic intrafraction motion and they report intrafraction motion to be less than 1 mm and comparable to our results 13. (a) is without OSMS and (b) is with OSMS portal imaging was used for relative measurements to get a more realistic intrafraction motion and they report intrafraction motion to be less than 1 mm and comparable to our results 13.…”
supporting
confidence: 81%
“…In this study, using a virtual bolus, we focused on taking into account interfraction movements. Indeed, a systematic review covering 3378 studies concluded that interfraction motion is larger than intrafraction32 which was confirmed in another recent study 33…”
Section: Discussionmentioning
confidence: 79%
“…The measured data were then verified by both the medical physicist and the radiation oncologist. According to the methods reported in previously published articles, the measurements were performed on portal images (Figure 1 ), so that the lateral shifts could not be quantified ( 6 , 7 , 11 , 12 ).…”
Section: Methodsmentioning
confidence: 99%